Endoscopic Mucosal Resection for Esophageal and Gastric Mucosal Cancers - Haruhiro Inoue (Canadian Journal of Gastroenterology, 1998)
Accumulated data from surgically resected specimens reveal that mucosal cancers of the esophagus and stomach pose low risk of lymph node metastasis. The author used endoscopic mucosal resection (EMR) as curative treatment in 142 cases of esophageal cancer and 102 cases of stomach cancer. In absolutely indicated cases there has been no local or distant metastasis during the longest period of follow-up (nine years). One perforation and one post-treatment severe stenosis, which was resistant to dilation therapy in the esophagus, were encountered. Deeper layer resection (including partial proper muscle) occurred in the stomach in three cases where the lesions were positioned to the lesser curvature of the upper part of the stomach. Two cases of gastric mucosal resection leaving residual cancer were successfully treated by laser ablation. No case has required further surgery. Resected specimens were contributed to histological evaluation in all cases. In conclusion, EMR can be considered as the first-line treatment for selected cases of early stage esophageal and stomach cancer.